C/EBPβ in Alzheimer’s disease: An integrative regulator of pathological mechanisms - Xiaoting Luo; Junyi Liang; Xue Lei; Fengqi Sun; Minghai Gong; Bin Liu; Zhongguang Zhou (Brain Research Bulletin)
Alzheimer's disease (AD) stands as one of the most prevalent neurodegenerative disorders, characterized by a progressive decline in cognitive function, neuroinflammation, amyloid-beta (Aβ) plaques, and neurofibrillary tangles (NFTs). With the global aging population, the incidence of AD continues to rise, yet current therapeutic strategies remain limited in their ability to significantly alleviate cognitive impairments. Therefore, a deeper understanding of the molecular mechanisms underlying AD is imperative for the development of more effective treatments. In recent years, the transcription factor C/EBPβ has emerged as a pivotal regulator in several pathological processes of AD, including neuroinflammation, lipid metabolism, Aβ processing, and tau phosphorylation. Through intricate post-translational modifications, C/EBPβ modulates these processes and may influence the progression of AD on multiple fronts. This review systematically explores the multifaceted roles of C/EBPβ in the pathogenesis of AD, delving into its crucial involvement in neuroinflammation, Aβ production, tau pathology, and lipid metabolism dysregulation. Furthermore, we critically assess therapeutic strategies targeting C/EBPβ, examining the challenges and opportunities in regulating this factor. By synthesizing the latest research findings, we offer a more comprehensive understanding of the role of C/EBPβ in AD and discuss its potential as a therapeutic intervention target.